Staging deaths: King Sverre or a usurper's path to the throne - Brégaint,David (2018)
The present study explores how the Norwegian usurper, King Sverre (1184-1202) exploited three princely burials to overthrow the ruling king and establish his dynasty. Both in 1179 and 1184, King Sverre took full advantage of his military victories to gain popular support for his claims to the throne, in transforming the burial of his most prominent enemies felt on the battlefield into a rostrum for his political propaganda, through speeches and ritual staging. Sverre's own agony and funerals were also meticulously staged in order to defend his rule from accusations of excommunication and pave the way for his succession. The study provides insights on the challenges met by a usurper on his way to royal power and, in particular, on the concomitant relationship between military combat and the work of political persuasion